SIBOX Smart Loker System with Dynamic Systems Development Method - Untoro, Meida Cahyo; Praramadhana, Daffa; Suranta, Akmal Fauzan; Amrulloh, Iqbal; Praseptiawan, Mugi (Teknik: Jurnal Ilmu Teknik dan Informatika, 2023)
At this time logistics companies have a very important role in everyday life, especially in package delivery. The high level of online shopping is one of the reasons why the role of logistics is very important in our daily lives. Thus, seeing the common problems that occur in the conventional logistics delivery process, we came up with the idea to create an integrated smart locker to be one of the replacements for existing logistics outlets, we hope that with this application we can reduce the company's logistics expenses used in procuring logistics outlets and make it easier for couriers to work in the package delivery process. We created this application using a microservices architecture with the SDLC method used is Agile Dynamic System Development (DSDM). React JS framework as an interface and Express js and Laravel as an application that works behind the interface. The idea that we initiated we raised as a project within the company with the client from the company. In the end, the smart locker program made using the DSDM method has been completed and is ready to be implemented in the company and the client